STATUS HUKUM HAK MILIK ATAS TANAH YANG TERKENA ABRASI - Susiati, Dwi; Setiadji, Sri (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Abrasion is a natural disaster that results in the owner of the right to land losing the right to control, use or take advantage of the land, because the land is lost in part or in whole due to erosion by water. Article 27 of the Law On Agraria determines that property rights over land are destroyed if the land is destroyed. In this study, the author will analyze the legal status of property of land affected by abrasion with the formulation of the problem What is the legal status of property rights on land affected by abrasion according to Government Regulation Number 24 of 1997 concerning Land Registration and how to guarantee the protection of affected land rights abrasion. The results of this study are that the status of land rights affected by abrasion is abolished, both in the provisions of the Law On Agraria and Government Regulation Number 24 of 1997 concerning Land Registration because it is no longer compatible with physical data or juridical data as a strong evidence. The government has an obligation to provide guarantees and protection of rights to land affected by abrasion and those that have been affected by abrasion in part or in whole. On the basis of the state's right to control Article 2 of the Law On Agraria the state has the right to regulate land use, inventory, and maintenance to prevent and reduce the impact of abrasion on its citizens. The government can also provide compensation as contained in Article Number 24 of 2007 concerning Disaster Management which determines that the Government and regional governments are responsible for the implementation of disaster management.Abrasi merupakan bencana alam yang mengakibatkan pemilik hak atas tanah kehilangan hak untuk menguasai, menggunakan, atau mengambil manfaat atas tanah, karena tanah tersebut hilang sebagian atau seluruhnya akibat pengikisan oleh air. Pasal 27 UUPA menentukan hak milik atas tanah hapus, apabila tanahnya musnah. Pada penelitian ini, penulis akan menganalisa tentang status hukum hak milik atas tanah yang terkena abrasi dengan rumusan masalah Bagaimana status hukum hak milik atas tanah yang terkena abrasi menurut PP No. 24 Tahun 1997 tentang Pendaftaran Tanah dan bagaimana jaminan perlindungan hak-hak tanah yang terdampak abrasi. Hasil dari penelitian ini adalah bahwa status hak atas tanah yang terkena abrasi adalah hapus, baik dalam ketentuan UUPA maupun PP No. 24 Tahun 1997 tentang Pendaftaran Tanah karena tidak sesuai lagi dengan data fisik maupun data yuridis sebagai alat bukti yang kuat. Pemerintah mempunyai kewajiban untuk memberikan jaminan dan perlindungan hak-hak atas tanah yang terdampak abrasi maupun yang sudah terkena abrasi baik sebagian maupun seluruh tanahnya. Atas dasar hak menguasai oleh negara Pasal 2 UUPA negara berhak mengatur peruntukan, penggunaan, persediaan,dan pemeliharaan tanah untuk mencegah dan mengurangi dampak abrasi bagi warga negaranya. Pemerintah juga dapat memberikan ganti kerugian sebagaimana yang ada di dalam UU No. 24 Tahun 2007 tentang Penanggulangan Bencana yang menentukan bahwa Pemerintah dan pemerintah daerah menjadi penanggung jawab dalam penyelenggaraan penang-gulangan bencana.